Profile of Physical Condition of University Soccer Players Who Train at Moderate Altitude - Rivera Joven, Angie Shirley (2020)
Objective: To determine the physical condition of university soccer players from Bogotá, Colombia, who train at moderate altitude. Method: Quantitative descriptive and cross-sectional study conducted on 191 university soccer players (84 midfielders, 49 defenders, 38 forwards, and 20 goalkeepers), with age averages of 19,9 ± 1,83, weight 66,4 ± 8,88, height 171 cm ± 0,5, and a body mass index of 22,5 ± 2,52 kg/m2. Physical fitness tests were applied, such as horizontal jump (SH), sit and reach (SR), speed test at 30 m from a static exit (T30M) and shuttle run (SHR), body composition and cardiovascular resistance tests. Course navette (SRT-20m) and Cooper (CRT) were evaluated. Data are presented as means and standard deviations. The results by playing position were compared using one-way analysis of variances (ANOVA), and post-hoc tests were run (Gabriel) for those that were significant (p≤0,05). Results: A post-hoc analysis of Gabriel was performed; it showed significant differences between the group of defenders and midfielders (p = 0,05). All the variables met the assumption of homogeneity of variances. The only variable that showed a significant difference was the long jump (F3-190 = 3,139; p= 0,027). Conclusions: Significant differences were observed between the group of defenses and midfielders, which may be associated with the motor pattern, variations in strength, speed, muscle power, and rhythm changes that each position has within the game.